A Novel Approach for Fluoroscopic Guided Intra-articular Hip Injections: Technique Description and Case Series. (27th September 2022) - Santana De Los Santos, Javier Antonio; Cross, Aaron; Castaneda, Pablo; Sherman, Andrew L.
Abstract: Fluoroscopic guided intra-articular hip injections generally utilize a standard anterior-posterior view. However, this approach can expose patients to inadvertent femoral nerve or vessel infiltration owing to the proximity of the neurovascular bundle to the joint space. This case-series study describes a novel technique using fluoroscopic ipsilateral oblique angulation and caudal tilt of the image intensifier. With this view, the clinician can advance the needle in a lateral to medial trajectory to obtain intra-articular access and minimize the risk of complications. This method was performed in five patients with refractory chronic hip osteoarthritis, which resulted in notable pain improvements and no reported adverse events. The suggested technique could provide a safer alternative to the anterior-posterior imaging technique for intra-articular hip injections by avoiding the femoral neurovascular bundle, limiting needle repositioning, and offering a satisfactory postprocedural analgesic effect.